Curative treatment of pancreatic functioning insulinoma with stereotactic ablative radiation therapy: case report - Alsuhaibani, Aws Abdulrahman; Alsuhaibani, Abdullah Abdulrahman; Hassan, Tareq Salah (International Surgery Journal, 2021)
Insulinoma is the most common pancreatic neuroendocrine tumor (NET). It is a rare disease account for 1-2% of pancreatic tumors and affect approximately up to 3 patients per million per year. complete surgical resection or debulking are standard of care option. However, surgery is associated with short and long-term post-operative morbidity and may not be appropriate for all patients. In This case we present management and cure of a case of functioning insulinoma with stereotactic ablative radiosurgery in an unfit patient for surgery.